2008
DOI: 10.1016/j.brainres.2008.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal opiate exposure impairs radial arm maze performance and reduces levels of BDNF precursor following training

Abstract: Prenatal exposure to opiates, which is invariably followed by postnatal withdrawal, can affect cognitive performance. To further characterize these effects, we examined radial 8-arm maze performance and expression of brain derived neurotrophic factor (BDNF) in male rats prenatally exposed to the opiate l-α-acetylmethadol (LAAM). Female rats received 1.0 mg/kg/day LAAM or water via daily oral gavage for 28 days prior to breeding, during breeding, and throughout pregnancy. Pups were fostered to non-treated lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…Animal studies also suggested that the learning ability and cognitive abilities were reduced in offsprings prenatally exposed to heroin,31,38 morphine,31,39 L-alpha-acetylmethadol,40 or methadone 4143. The current study also revealed that cognitive function of offsprings was impaired after prenatal buprenorphine exposure, suggesting that prenatal exposure to different types of opioids might interfere with learning abilities and memory formation through their common site of action in the opioid system.…”
Section: Discussionsupporting
confidence: 60%
“…Animal studies also suggested that the learning ability and cognitive abilities were reduced in offsprings prenatally exposed to heroin,31,38 morphine,31,39 L-alpha-acetylmethadol,40 or methadone 4143. The current study also revealed that cognitive function of offsprings was impaired after prenatal buprenorphine exposure, suggesting that prenatal exposure to different types of opioids might interfere with learning abilities and memory formation through their common site of action in the opioid system.…”
Section: Discussionsupporting
confidence: 60%
“…10 These alterations were often accompanied by behavioral changes. Rats exposed prenatally to a long-acting opiate demonstrated more reference and working memory errors in the radial arm maze 11 , and postnatal morphine exposure impaired reward-mediated learning in adulthood. 12 …”
mentioning
confidence: 96%
“…The development of the prenatal oxycodone treatment paradigm is described in detail in [28]. Nulliparous female (64–70 days of age) Sprague-Dawley rats (Harlan, Indianapolis, IN) were treated with oxycodone HCl (Mallinckrodt, St. Louis, MO) or the water vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we developed a model in which prenatal opiates are administered before and during the entire gestational period. Previous work in our laboratory using this approach with prenatal exposure to LAAM found poor performance in acquisition of the radial arm maze, a spatial memory task [28]. Prenatal LAAM-exposed rats had more reference and working memory errors, but were able to acquire the task after five days of training.…”
Section: Introductionmentioning
confidence: 99%